Humidity‐Induced Simultaneous Visible and Fluorescence Photonic Patterns Enabled by Integration of Covalent Bonds and Ionic Crosslinks. (19th September 2021) - Lan, Ruochen; Wang, Qian; Shen, Chen; Huang, Rui; Bao, Jinying; Zhang, Zhongping; Zhang, Lanying; Yang, Huai
Abstract: Stimuli‐responsive photonic crystals (PCs) have been extensively studied due to their potential in fabrication of anti‐counterfeiting devices and information storage. In this work, using Ca 2+ ionic crosslinker, a cholesteric liquid crystalline network (CLCN) based PC able to simultaneously present visible and fluorescence pattern by moisture treatment is designed and prepared. The circularly polarized light from helical structure of CLCN makes the reflected pattern distinguishable under different circular polarizer, implying the unique advantage of this novel coating as anti‐counterfeiting devices. More importantly, due to the thermochromic property of the liquid crystal monomers, permanent pattern is achievable by chemically crosslinking specific region at different temperature. By integrating chemically crosslinking and physically ionic crosslinking, a permanent pattern and a dynamic humidity responsive pattern can be incorporated in a single device, indicating the great potential of this novel photonic coating in information storage. Abstract : Humidity responsive photonic coating with simultaneous visible and fluorescence pattern is prepared by ionically crosslinking the fluorescence changeable cholesteric liquid crystalline network (CLCN). More importantly, integrating the covalent bonding and ionic crosslinking enables the CLCN coating to display permanent pattern and dynamic pattern, indicating its potential in fabrication of anti‐counterfeiting devices and information storage.